Modern Judaism an Oxford guide - De Lange, N. R. M. (Nicholas Robert Michael), 1944-; Freud-Kandel, Miri. (Oxford ; New York : Oxford University Press, 2005)
"A multi-disciplinary, multi-authored guide to Jewish life and thought. This book covers the major areas of thought in Jewish Studies, including considerations of religious differences, sociological, philosophical, and gender issues, geographical diversity, inter-faith relations, and the impact of the Shoah (the Holocaust) and the modern state of Israel" --Provided by publisher.
Includes index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2023. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Judaism; Jews; Electronic books